Examining the software piracy problem through the case of the Macedonian economy - Aleksandar Petkovski; Jovanka Damoska (UTMS Journal of Economics, 2021)
There is an ongoing conflict between software copyright owners and a vast majority of users who are continually finding ways to use the software without paying. The paper investigates the attitudes of the users towards application of licensed or unlicensed software. Through in-debt analysis of the focus group of software users on one hand and the official authorities responsible for implementation of copyrights regulation the paper identifies the reasons behind the actual situation of software using in the Macedonian economy. The officials do not invest any serious effort in the implementation of the copyrights protection legislation. The main arguments of the users, for opting to use unlicensed software, are the low purchasing power of people in Macedonian economy and the high software prices. The actual situation is unsustainable from legal, ethical, and economic aspects. A possible way out of this situation would entail software producers adjusting the prices of their products to the average purchase power of the Macedonian citizens, and the state should stop tolerating software piracy and display consistency in the implementation of copyright protection legislation.
Keywords: O34; K42; E31; E01; 330; licensed software; unlicensed software; copyright; purchasing power; legislation